Social Dangerous Consequences as an Objective Element of the Corpus Delicti - Mitreva, Petya (Research Papers, 2020)
Criminal law theory supports that the socially dangerous consequences are included in the construction of so-called material corpus delicti and the formal corpus delicti do not contain consequences in their construction. The article examines the question of the classification criterion for the division of formal and material corpus delicti, using the methods of analysis and synthesis, the comparative method and the methods of interpretation in law. The analysis is based on the thesis that all of the crimes cause socially dangerous consequences - negative objective changes in their object. As a result of the study, the author concludes that the consequences of the crimes are included in both the material corpus delicti and the formal corpus delicti, but with different legislative techniques for describing them.